2020
DOI: 10.1002/jmv.25917
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory syncytial virus in influenza‐like illness cases: Epidemiology and molecular analyses of four consecutive winter seasons (2014‐2015/2017‐2018) in Lombardy (Northern Italy)

Abstract: Background Besides seasonal influenza viruses (IV), several other pathogens—including respiratory syncytial virus (RSV)—are involved in clinically undistinguished influenza‐like illnesses (ILIs). This study aimed at investigating the contribution of RSV in ILI cases in Lombardy (Northern Italy) during four consecutive winter seasons. Materials and Methods In the framework of influenza surveillance, respiratory samples from ILI outpatients were collected from 2014‐2015 to 2017‐2018 season. IV‐negative swabs wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(60 citation statements)
references
References 34 publications
7
53
0
Order By: Relevance
“…During the study period, RSV circulated from mid-November until the end of April, peaking in mid-February (median: week 8; range: 6–10); the duration of RSV circulation was about 4 months (median: 15.5 weeks; range: 13–19 weeks). This is consistent with the results of a previous analysis of data from 15 European countries, which did not include Italy [ 41 ].
Fig.
…”
Section: Epidemiological Surveillancesupporting
confidence: 93%
See 1 more Smart Citation
“…During the study period, RSV circulated from mid-November until the end of April, peaking in mid-February (median: week 8; range: 6–10); the duration of RSV circulation was about 4 months (median: 15.5 weeks; range: 13–19 weeks). This is consistent with the results of a previous analysis of data from 15 European countries, which did not include Italy [ 41 ].
Fig.
…”
Section: Epidemiological Surveillancesupporting
confidence: 93%
“…RSV was detected in all age groups; however, the RSV positivity rate among ILI cases was highest in the pediatric age group ≤5 years (27.8%; 51/183) (Table 2 ) [ 41 ].…”
Section: Epidemiological Surveillancementioning
confidence: 99%
“…As the regional reference laboratory for influenza and other respiratory viruses in Lombardy, we collaborate closely with the national COVID-19 surveillance system coordinated by the National Institute of Health (Istituto Superiore di Sanità, ISS), and soon after the global spread of SARS-CoV-2 was announced, we implemented SARS-CoV-2 molecular detection as part of the ILI sentinel surveillance program [8]. In fact, since ILI clinical manifestations are similar to mild symptoms of SARS-CoV-2 infection, the Italian Influenza Surveillance Network (InfluNet) was used to monitor the epidemiological and virological characteristics of SARS-CoV-2, which had previously been employed successfully for respiratory viruses other than influenza, such as respiratory syncytial virus (RSV) [9], enteroviruses, and parechoviruses [10]. Recently, it has been demonstrated that ILI outpatient surveillance data could be used to estimate the baseline prevalence of SARS-CoV-2 and to identify surges of excess ILIs correlated with SARS-CoV-2, with the broader potential to use this syndromic surveillance for early detection and molecular-epidemiological characterization [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Respiratory syncytial virus (RSV) is a single-stranded RNA virus that belongs to the Paramyxoviridae family, affecting respiratory epithelial cells and presenting two subtypes, RSV A (the most severe form of presentation) and RSV B [ 1 ].…”
Section: Introductionmentioning
confidence: 99%